THE CLINICAL SIGNIFICANCE OF INTERLEUKIN-4 IN SYSTEMIC SCLERODERMA - Eshmuratov Sardor Eldorovich; Uralov Rustam Sherbekovich (Journals Park Publishing, 2024)
Goal. To study the relationship of serum interleukin-4 (IL-4) levels with visceral pathology, the nature of the course and clinical forms of SSD. Materials and methods. IL-4 was determined in the sera of 40 patients with SSD by indirect solid-phase enzyme immunoassay (ELISA). Results. The level of IL-4 in the range of 10-1000 pg/ml was detected in 12 out of 40 patients with SSD (30%). The distinctive features of this group of patients were a shorter duration of the disease, progression of cutaneous fibrosis and visceral pathology by the time of examination and a tendency to a higher incidence of pulmonary fibrosis. There were no significant differences in the lesion of other internal organs, as well as the dependence of the IL-4 content on the clinical forms and course of the disease. In patients with an increase in IL-4 in the blood showed higher levels of CIC, u-globulins, while the content of acute-phase reactants was lower than in the rest of the group. Conclusion. The established association of serum IL-4 levels with the activity of the fibrous process in SSD requires confirmation in prospective studies.
Keywords: interleukin-4. T lymphocytes, fibrosis, activity, systemic scleroderma.